Isolated idiopathic radial artery aneurysm in an infant - Darren M. Fiore; Rym El Khoury (Elsevier, 2022)
A 5-month-old girl presented with an enlarging pulsatile mass of the right forearm. There was no preceding trauma to the arm. Vascular imaging and arteriography confirmed an isolated true aneurysm of the proximal radial artery. The aneurysm was surgically resected, and the infant recovered uneventfully with no recurrence of the aneurysm. Isolated peripheral arterial true aneurysms, although exceedingly uncommon in children, should be considered in the differential diagnosis of a pulsatile extremity mass.